Indirect effects of gender on illness behavior through psychosocial factors and perceived stress - Thomas, Jenifer J., author; Borrayo, Evelinn A., advisor (Colorado State University. Libraries, 2008)
Gender differences that have been found in illness behavior, such as reporting symptoms and utilization of health services, can be partially explained by social, psychological, and/or behavioral factors (Denton & Walters, 1999; Denton, Prus, & Walters, 2003). The indirect influence of gender through such factors may further explain differences in illness behavior. The purpose of this study was to determine how the effect of gender on illness behavior may be influenced by social support satisfaction, perceived health status, coping skills, and perceived stress by testing various path models. Secondary analysis of previously collected data from 303 college students were used. A confirmatory factor analysis was performed to test indicators of the underlying latent variables (i.e. social support satisfaction, coping skills, and perceived stress). Four path models tested the patterns of effects between the latent variables. The main findings of the final model show the relationship between gender and illness behavior was influenced by three paths of indirect effects through multiple factors. The first was the combined influence of gender, greater use of total coping skills, greater social support satisfaction, low perceived stress, and good perceived health status on less reported illness behavior. The second was the combined influence of gender, greater use of total coping skills, greater social support satisfaction, and low perceived stress on less reported illness behavior. The third was the combined influence of gender, high perceived stress, and poor perceived health status on more reported illness behavior. The use of multiple health-related factors may provide a more complete picture of how gender and psychosocial factors influence illness behavior. Future studies should consider testing separate models by gender to better understand how the direction of the variables of interest impact illness behavior differently among men and women.
Keywords: gender; illness behavior; influences on illness behavior; psychological stress; social psychology; clinical psychology; health education